Implementation of Islamic Religious Education (PAI) Learning at SDN Cadangpinggan 3 Sukagumiwang District, Indramayu Regency - Nur Ajijah Rajak; Akhmad Mujani; Abdul Aziz Romdhoni (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Learning Islamic Religious Education in elementary schools aims to reveal the concept of learning Islamic religious education in elementary schools. In its development, elementary school age children have their own characteristics, the ability of children to think of elementary school age children develops gradually. It needs to be understood wisely to be able to deliver the success of educational goals. This research uses field research methods. The field research method is a method of collecting data in qualitative research which does not require in-depth knowledge of the literature used and certain abilities on the part of the researcher. The method used during the activity is to use the teaching method. This teaching method is used when delivering Islamic religious education learning materials, practices, and discussions in the middle of the material and at the end of the delivery of the material. If there are participants who want to ask questions, participants can ask the speaker. The conclusion in this method students can understand Islam as a whole, live it, and in the end can practice and make Islam a way of life. As well as making the students of SDN Candanpinggan 3 in Sukagumiwang Village work well.